2013
DOI: 10.1101/gr.157008.113
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput chromatin motion tracking in living yeast reveals the flexibility of the fiber throughout the genome

Abstract: Chromosome dynamics are recognized to be intimately linked to genomic transactions, yet the physical principles governing spatial fluctuations of chromatin are still a matter of debate. Using high-throughput single-particle tracking, we recorded the movements of nine fluorescently labeled chromosome loci located on chromosomes III, IV, XII, and XIV of Saccharomyces cerevisiae over an extended temporal range spanning more than four orders of magnitude (10 -2 -10 3 sec). Spatial fluctuations appear to be charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
207
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(251 citation statements)
references
References 62 publications
34
207
2
1
Order By: Relevance
“…The prefactor C characterizes how fast the chromatin locus moves, the exponent is indicative of the type of diffusion, subdiffusive if α<1 or diffusive if α=1 (in this latter case, C would be identical to the diffusion coefficient). Our finding that α≈0.5 is in agreement with previous studies on other chromosome loci, which have reported subdiffusion with similar exponents in both prokaryotes and eukaryotes Hajjoul et al, 2013;Weber et al, 2010). This shows that subtelomeres undergo subdiffusive motion.…”
Section: Antagonistic Effects Of Csm4 and Polymerized Actin On Subtelsupporting
confidence: 93%
See 3 more Smart Citations
“…The prefactor C characterizes how fast the chromatin locus moves, the exponent is indicative of the type of diffusion, subdiffusive if α<1 or diffusive if α=1 (in this latter case, C would be identical to the diffusion coefficient). Our finding that α≈0.5 is in agreement with previous studies on other chromosome loci, which have reported subdiffusion with similar exponents in both prokaryotes and eukaryotes Hajjoul et al, 2013;Weber et al, 2010). This shows that subtelomeres undergo subdiffusive motion.…”
Section: Antagonistic Effects Of Csm4 and Polymerized Actin On Subtelsupporting
confidence: 93%
“…This is in agreement with previous studies, which have shown that locus motion does not obey free diffusion but is instead constrained with a subdiffusive behavior that is ubiquitously observed in bacteria, yeast and mammals (Heun et al, 2001;Marshall et al, 1997;Weber et al, 2012). The observed subdiffusive exponent is consistent with the Rouse model of polymer dynamics that assumes spring-like interactions between consecutive monomers, or alternatively with a viscoelastic response of the nuclear medium (Bronstein et al, 2009;Cabal et al, 2006;Hajjoul et al, 2013;Lucas et al, 2014;Weber et al, 2012). Although the anomalous exponent does not depend on the locus, the prefactor C shows variations relative to the genomic position, as exemplified by the reduced mobility of subtelomeres (Bystricky et al, 2005;Hajjoul et al, 2013;Heun et al, 2001).…”
Section: Interphase Subdiffusive Chromatin Dynamics Requires Actinsupporting
confidence: 92%
See 2 more Smart Citations
“…Examples include az0:7 for RNA-protein particles in E. coli (14,21) and S. cerevisiae (22), az0:7 for lipid granules in fission yeast (23), az0:5 for gold nanoparticles in several human and mammalian cell lines (24), and az0:5 À 0:8 for dextrans in HeLa cells (25). Chromosomal loci also exhibit subdiffusive behavior, with az0:4 À 0:5 for E. coli (26,27), az0:5 À 0:7 in budding yeast (28,29), and az0:3 for mammalian telomeres at timescales <10 s (30). Note that subdiffusive behavior does not necessarily imply nonGaussian behavior, as models such as fractional Brownian motion exhibit Gaussian, anticorrelated increments resulting in anomalous diffusion (31).…”
Section: Introductionmentioning
confidence: 99%